Whither Kampung Sawah Bekasi: A Model For Religious Moderation Practice? - Ahmad Ali Nurdin; Adon Nasrullah Jamaludin (UIN Sunan Gunung Djati Bandung, 2025)
This article examines the practice of religious moderation in Kampung Sawah, Bekasi, an area known for its high level of religious diversity and longstanding traditions of harmonious interfaith relations. Although the concept of religious moderation was formally introduced by the Indonesian Ministry of Religious Affairs only in recent years, this study finds that the community of Kampung Sawah has long embodied similar values in their everyday social practices. Using a descriptive-analytical method, the research identifies that the four key indicators of religious moderation—national commitment, tolerance, non-violence, and appreciation of local culture—are strongly reflected in the attitudes and behaviors of the community. These moderate orientations have emerged through a long socio-cultural process, shaped by value transmission within families and sustained interactions within the broader community. A central mechanism in this formation is the community’s consistent emphasis on shared identity and collective harmony over religious or cultural differences. The findings demonstrate that religious moderation can evolve organically through historical experience, cultural continuity, and community-based social relations.